2008
DOI: 10.1086/588017
|View full text |Cite
|
Sign up to set email alerts
|

Merging of Globular Clusters in Inner Galactic Regions. II. Nuclear Star Cluster Formation

Abstract: In this series of papers, we present the results of detailed N-body simulations of the interaction of a sample of four massive globular clusters in the inner region of a triaxial galaxy for two different sets of initial conditions that correspond to different initial density concentrations. A full merging of the clusters takes place, leading to a slowly evolving cluster that is quite similar to observed nuclear clusters. Actually, both the density and the velocity dispersion profiles match qualitatively, and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 48 publications
7
52
0
Order By: Relevance
“…Agarwal and Milosavljević (2011) modeled the infall (and stripping) of globular clusters analytically and concluded that this process could create NSCs which match the observed NSC masses. Capuzzo-Dolcetta and Miocchi (2008a) show that globular clusters merging at the center of a bulge leads to density-velocity dispersion properties consistent with those of observed NSCs. Analytic modeling of the infall of globular clusters led Gnedin et al (2014) to the same conclusion; they argue, moreover, that the contrast between the NSC and the background galaxy would be much lower in a massive galaxy like M87, making them harder to detect in such systems.…”
Section: Nuclear Star Clusterssupporting
confidence: 64%
“…Agarwal and Milosavljević (2011) modeled the infall (and stripping) of globular clusters analytically and concluded that this process could create NSCs which match the observed NSC masses. Capuzzo-Dolcetta and Miocchi (2008a) show that globular clusters merging at the center of a bulge leads to density-velocity dispersion properties consistent with those of observed NSCs. Analytic modeling of the infall of globular clusters led Gnedin et al (2014) to the same conclusion; they argue, moreover, that the contrast between the NSC and the background galaxy would be much lower in a massive galaxy like M87, making them harder to detect in such systems.…”
Section: Nuclear Star Clusterssupporting
confidence: 64%
“…The first simulations were done by (Capuzzo-Dolcetta & Miocchi 2008b) and (Capuzzo-Dolcetta & Miocchi 2008a) in galaxy models without massive black holes and stellar discs; (Bekki 2010) studied the role of stellar discs and the role of a central galactic MBH.…”
Section: Introductionmentioning
confidence: 99%
“…Two main scenarios have been suggested for the formation of NSCs: i) infall of star clusters that formed elsewhere in the host galaxy (Tremaine et al 1975;Capuzzo-Dolcetta & Miocchi 2008); ii) in situ formation and build-up through star formation following the accretion of gas in the centre of the galaxies. Bekki (2007) performed chemodynamical simulations of the inner regions of dwarf galaxies, where dissipative merging of stellar and gaseous clumps formed in the spiral arms can lead to the formation of NSCs.…”
Section: Introductionmentioning
confidence: 99%